Teaching receptive vocabulary to two autistic children: A replicated, clinic-based, single case experimental design - Rebecca Gray; Deirdre M Muldoon; Emily B. McCarthy (Autism and Developmental Language Impairments, 2024)
Background and aims This study was conducted in a clinical setting with the aim of replicating previously used procedures for teaching receptive vocabulary. Researchers increased the number of vocabulary words and maintained use of match-to-sample (MtS), prompting, and reinforcement procedures. Researchers were also interested in the efficacy of the intervention from caregivers’ perspectives. Methods Using a concurrent multiple baseline design, two autistic preschoolers with receptive language impairment were taught to identify 30 common objects. MtS, prompting, and reinforcement procedures were individualized to support each child. Maintenance checks and generalization probes were completed after a predetermined number of intervention sessions (i.e. three or four clinic sessions). A social validity questionnaire was completed by parents following the final maintenance check. Results Receptive object identification improved significantly for both participants. Despite exposure to vocabulary targets for only three or four sessions, they generalized the vocabulary targets to non-identical pictures and maintained words at maintenance checks. Participants were most successful when researchers individualized prompting and reinforcement. Conclusion MtS, prompting, and reinforcement were effective procedures for improving object identification, even with a limited number of intervention sessions. To support varying learner profiles, modifying prompting and reinforcement procedures was necessary. Caregivers of both participants reported positive improvements in areas such as communication, attention, and behaviors. Implications This replicated study provides support for MtS, prompting, and reinforcement as means of teaching receptive vocabulary to autistic preschoolers in a clinical setting. The materials used were simple and cost-effective. Overall, this study outlines and supports a flexible and effective evidence-based practice to teach receptive language to autistic children.